The Effects of University Leadership Management: Efforts to Improve the Education Quality of State Institute for Islamic Studies (IAIN) of Bengkulu - Khairiah Khairiah; Sirajuddin Sirajuddin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2019)
The study of paper aims to describe efforts to improve the quality of an institution University of leadership management. The method uses a quantitative approach and path analysis. The point management institution is the academic education quality and the reputation of the university's publications which is the Tridarma statute for Higher Education in teaching-learning, research approach, and community service. Scientific publications are a starting point for global involvement in Higher Education management. Higher education management shows from Webometrics as an international recognition database for university rankings. It sees on the accreditation institutions such as ISO, National Accreditation for Higher Education as a quality service assessment bodies for Higher Education, e-Journal as a scientific publication agency in the publishing management network for papers written by lecturers and research findings of universities, and International office as an institution for national and international partnerships to achieve organizational success. The paper discusses 4 official Leadership Management Programs to improve the quality of the Bengkulu State Islamic Institute (IAIN Bengkulu). Keywords: Management, Employee Leadership, Education Quality Abstrak Kajian tulisan ini bertujuan untuk mendeskripsikan upaya peningkatan mutu pendidikan dalam kajian manajemen kepemimpinan pegawai. Adapun metode yang digunakan dengan pendekatan kuantitatif dan teknik analisis jalur. Komponen yang menjadi tolak ukur adalah mutu akademik pendidikan dan reputasi publikasi Perguruan Tinggi. Dua hal tersebut disebutkan dalam Tridarma Perguruan Tinggi pada pengajaran, penelitian dan pengabdian masyarakat. Publikasi ilmiah adalah wadah awal adanya keterlibatan dunia global dalam manajemen perguruan tinggi. Manajemen perguruan tinggi dapat dilihat dari Webometrics sebagai database pengakuan Internasional pada ranking indek perguruan tinggi, lembaga akreditasi seperti ISO, BAN-PT adalah badan penilai mutu layanan Perguruan tinggi, e-Journal sebagai lembaga publikasi ilmiah dalam jaringan manejemen penerbitan artikel para dosen dan hasil penelitian perguruan tinggi, Internasional office adalah lembaga kerjasama baik nasional dan internasional pada pencapaian kesuksesan organisasi. Artikel membahas 4 Program Pengaruh Manajemen Kepemimpinan Pegawai dalam upaya menigkatkan mutu IAIN Bengkulu. Kata Kunci: Manajemen, Kepemimpinan Pegawai, Mutu Pendidikan